THE USE OF TALK-SHOW VIDEO AS A REFLECTIVE PRACTICE TO IMPROVE STUDENTS’ VOCABULARY IN ENGLISH SPEAKING SKILL - Syahadati, Elly (Jurnal Pendidikan Bahasa, 2016)
This research is aimed to: (1) identity whether and to what extent talk show video as a reflective practice improved students’ vocabulary in speaking skill and (2) describe classroom climate when talk show video as a reflective practice was applied in the speaking class. The method used in this research was classroom action research. The research findings showed that talk show video in teaching and learning English could improve the students’ vocabulary in speaking skill and the classroom climate. Video could stimulate and motivate students’ interesting in improving their vocabulary in speaking class. As a result, talk show video is suitable for supporting and improving students’ speaking skill, it has important role in teaching and learning process. Keywords: talk show video, , speaking skill.